Collaborative Innovation in the Public Sector – New Perspectives on the Role of Citizens? - Agger, Annika; Hedensted Lund, Dorthe (Scandinavian Journal of Public Administration, 2017)
Collaborative innovation in the public sector is increasingly used as a strategy for balancing citizens’ rising expectations for public services with limited public resources. This article suggests that public polices construct citizens as clients, consumers, or co- producers and thereby encourage or discourage certain behaviours, with different poten- tial contributions to innovation. The article conceptualises a new role, that of citizens’ as co-innovators, and offers an analytical model that can be used in future studies of how public managers can act as civic enablers by creating different spaces for public innova- tion on the basis of the applicable citizen role.